The concept of succession evasion: An invisible behavior in the organization - Tahmine Salehi; Mansoureh Ashghali-Farahani; Mohammadsaeed Mirzaee (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The opposite of succession planning is a new concept called succession evasion; A deep understanding of this concept helps to correct the training process of competent staff in nursing management. This study was conducted with the aim of explaining succession evasion as a new concept in nursing management; Also, as an invisible aspect of organizational behavior in the field of management. MATERIALS AND METHODS: The current research was conducted using a qualitative approach and conventional content analysis methods. The participants included nursing managers selected using the purposeful sampling method based on the entry and exit criteria. The code of research ethics and required permits were received. The method of semi-structured interviews was used to collect data, and the time of the interviews varied between 39 and 90 minutes. All data was recorded and transcribed. The method proposed by Graneheim and Lundman was used for data analysis. Guba and Lincoln's criteria were used for the accuracy and robustness of the data. MAXQDA software was used for data management. RESULT: The subcategories related to succession planning included "Fear of succession planning," "Talent suppression," "Belief in the permanence of the position," and "Obstructing the growth of others." CONCLUSION: Succession evasion as an undesirable organizational behavior had four primary categories, fear of succession planning, talent suppression, belief in-Popsition stability, and obstruction to the growth of others. It is recommended to use the findings of this study in the context of further explanation of the concept of succession evasion as the opposite of succession planning in future research, and also, to use this concept for planning nursing management.